HUBUNGAN PENGETAHUAN PERAWAT DAN BIDAN DENGAN KETERAMPILAN DALAM MEMBERIKAN PENDIDIKAN KESEHATAN INISIASI MENYUSU DINI PADA IBU PRENATAL DI PUSKESMAS KABUPATEN BATUBARA - Maimunah Maimunah R (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2017)
ABSTRACT Early breastfeeding initiation constitutes a process in which a baby begins to suckle on the breast by itself soon after it was born. Within the first hour, a baby must be breastfed by its mother. The aim was not only to give nutrition but also to train the baby to suck the nipple and to prepare the mother to produce colostrum breast milk. In the practice of giving early breastfeeding initiation, the skill of health care providers was very important in giving information through health education about early breastfeeding initiation for mothers. The skill of health care providers was closely related to their knowledge of early breastfeeding initiation.The objective of the research was to find out the correlation of the knowledge of nurses and midwives with the skill in providing health education about early breastfeeding initiation for prenatal mothers at Puskesmas of Kabupaten Batubara.The type of the research was descriptive analytic with cross sectional design. The population was 65 nurses and midwives who worked in KIA (Mother and Child Health), and 55 of them were used as the samples at the level of error 5%, using purposive sampling technique. The data were analyzed by using univatriate analysis with frequency distribution and bivatriate analysis with Spearman Rho test at the significance level of 5%. The result of the research showed that 40 respondents (72.7%), consisted of nurses and midwives, had good knowledge and 41 respondents (74.5%) had good skill which indicated that there was positive correlation between the knowledge of nurses and midwives and the skill in providing health education about early breastfeeding initiation for prenatal mothers at Puskesmas of Kabupaten Batu Bara with the result of coefficient correlation of -0.270 at the significance level p < α (0.047 < 0.05).It was recommended that the agency concerned determine and prepare the location for health counseling or education at the favorable site in order that the message or materials can achieve the target which was in line with the purpose of the expected health education. Keywords: Knowledge, Skill, Health Education